Mengenalkan Huruf Hijaiyah Dengan Menggunakan Media Handmade Pada Anak Usia Dini - Aziz, Mursal; Napitupulu, Dedi Sahputra; Marpaung, Khoirunnisah (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to analyze the application of handmade learning media in introducing hijaiyah letters in early childhood. This study uses the Classroom Action Research (PTK) method. The results of the study show that handmade media is effective in accelerating children's introduction to hijaiyah letters. This is based on the results of the initial test of students who completed only 11 people, with a classical completion percentage of 28.95%. Meanwhile, in the first cycle, there were 26 students who completed the course, with a classical completion percentage of 68.43%. Meanwhile, in the second cycle, the students who completed the program totaled 34 people, with a classical completion percentage of 89.47%.